Bi-modal distribution of stabilizers to regulate the dual-phase microstructure and transformability in Nd2O3/Y2O3-doped zirconia ceramics. Issue 14 (November 2019) - Chen, Wei; Hu, Dong-Li; Gu, Hui; Qian, Peng-Xiang; Vleugels, Jef; Jiang, Ying; Xing, Juan-Juan
Abstract: The phase relationship and microstructural characteristics were systematically studied for co-stabilized ZrO2 ceramics with Nd2 O3 –Y2 O3 additives coated onto starting powder. Polishing induced surface morphological changes by tetragonal-to-monoclinic transformation were observed by SEM. EDS analysis revealed a bi-modal distribution of the stabilizers correspondingly to smaller transformable tetragonal grains and larger non-transformable cubic grains. The correlation of co-stabilizer concentrations with the dual-phase microstructures leads to a probable two-stage sintering enabled by transient liquid-phase started from coating. Small t- ZrO2 grains inherited the starting nanopowder to take less stabilizers via diffusion, and larger c -ZrO2 grains incorporate directly stabilizers during growth from liquid-phase accumulated more stabilizers. The transformability of t- ZrO2 grains is influenced by neighboring c -ZrO2 grains when a compressive stress on the former is sufficiently large from the latter in larger size and high modulus, which could be regulated by the two-stage process to optimize the dual-phase microstructure.